Genome-Wide Assessment of Efficiency and Specificity in CRISPR/Cas9 Mediated Multiple Site Targeting in Arabidopsis. - Brenda A Peterson; David C Haak; Marc T Nishimura; Paulo J P L Teixeira; Sean R James; Jeffery L Dangl; Zachary L Nimchuk (PLoS ONE, 2016)
Simultaneous multiplex mutation of large gene families using Cas9 has the potential to revolutionize agriculture and plant sciences. The targeting of multiple genomic sites at once raises concerns about the efficiency and specificity in targeting. The model Arabidopsis thaliana is widely used in basic plant research. Previous work has suggested that the Cas9 off-target rate in Arabidopsis is undetectable. Here we use deep sequencing on pooled plants simultaneously targeting 14 distinct genomic loci to demonstrate that multiplex targeting in Arabidopsis is highly specific to on-target sites with no detectable off-target events. In addition, chromosomal translocations are extremely rare. The high specificity of Cas9 in Arabidopsis makes this a reliable method for clean mutant generation with no need to enhance specificity or adopt alternate Cas9 variants.